Micro-nano robots for treatment of eye diseases - Wang, Haocheng; Sun, Jingxue; Zhang, Xiaona; Zhou, Yingjie; Zhang, Yaguang; Ni, Yanan; Wang, Minnan; Wu, Yanmeizhi; Sun, Lulu; Zhao, Xiaoyu; Qiao, Hong (Frontiers in Chemistry, 2025)
In recent years, micro-nano robots have found extensive applications in the field of medicine. Among these, micro-nano robots demonstrate significant potential for the treatment of eye diseases. Micro-nano robots can penetrate eye tissue barriers to directly target the posterior segment of the eye for precise drug delivery, enabling non-invasive or minimally invasive treatment. This review explores the primary fabrication methods and propulsion mechanisms of various micro-nano robots, and their applications in treating various eye conditions, offering inspiration and guidance for advancing the use of micro-nanorobots in ophthalmic therapies.